Cover Feature: Determination of Aqueous Two‐Phase System Binodals and Tie‐Lines by Electrowetting‐on‐Dielectric Droplet Manipulation (ChemBioChem 2/2019). (9th January 2019) - Kojima, Taisuke; Lin, Chu‐Chi; Takayama, Shuichi; Fan, Shih‐Kang
Abstract : The cover feature picture shows biphasic droplets manipulated by electrowetting‐on‐dielectric (EWOD). We fabricated a "smart microscope slide" where aqueous droplets containing dextran (DEX) and poly(ethylene glycol) (PEG) macromolecules were prepared, mixed, and agitated by EWOD. In the droplets, liquid–liquid phase dynamics emerge depending on a DEX–PEG concentration, showing homogeneous, locally phase‐separated, or globally phase‐separated states. Facile observation of the droplets allows quantification of phase diagrams and sheds light on macromolecular crowding effects on liquid–liquid phase separation. More information can be found in the full paper by S. Takayama, S.‐K. Fan et al. onpage 270 in Issue 2, 2019 (DOI:10.1002/cbic.201800553 ).